2017
DOI: 10.1620/tjem.243.173
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence of Trunk or Lower Extremity Pain with Elbow and/or Shoulder Pain among Young Overhead Athletes: A Cross-Sectional Study

Abstract: Elbow or shoulder injuries are common in overhead sports. Because energy derived from the lower extremity passes through the trunk to the upper extremity in overhead motion, a break in such a kinetic chain could lead to arm injuries. However, there is only limited information about the role of the trunk and lower extremity support in preventing elbow or shoulder injuries. This study aimed to explore the association of trunk and lower extremity pain with elbow/shoulder pain among young overhead athletes. We con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 30 publications
(52 reference statements)
0
18
1
3
Order By: Relevance
“…Many previous studies on handball have not described the incidence rate of shoulder injuries in relation to the exposure, e.g. per 1,000 hours, but instead reported the number of shoulder injuries and the proportion of the total number of injuries or the prevalence of shoulder pain (40,44,48,65,67,68,70,74,85,94,(96)(97)(98)(99)(100). A summary of shoulder injuries and problems in handball is presented in Table 3.…”
Section: Shoulder Injuries In Handball 131 Incidence and Prevalencementioning
confidence: 99%
“…Many previous studies on handball have not described the incidence rate of shoulder injuries in relation to the exposure, e.g. per 1,000 hours, but instead reported the number of shoulder injuries and the proportion of the total number of injuries or the prevalence of shoulder pain (40,44,48,65,67,68,70,74,85,94,(96)(97)(98)(99)(100). A summary of shoulder injuries and problems in handball is presented in Table 3.…”
Section: Shoulder Injuries In Handball 131 Incidence and Prevalencementioning
confidence: 99%
“…We did not specify the degree of injury or whether it was the onset was acute or chronic for those in our injured group. Because a link between baseball players exhibiting throwing shoulder and elbow pain with knee and low back pain exists, clinicians should consider examining the trunk and lower extremities in those throwing athletes with an upper extremity injury 17 . However, based on the current findings, further examination into the TJA is warranted.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, when examining professional baseball pitchers, it was concluded that poor LPHC control was associated with missing significant time due to injury 2 . Subsequently, it was reported that there is a significant association between low back and knee pain with elbow and shoulder pain among youth baseball players 17 . Because of the relationship between weak LPHC and injury 2 17 , clinicians should consider a dynamic assessment that includes kinetic chain efficiency between the lower extremity and LPHC.…”
Section: Introductionmentioning
confidence: 99%
“…The following potential confounding factors were assessed using self-reported questionnaires and were included in this analysis as covariates: sex, age, body mass index (BMI, calculated using self-reported height and weight values), team levels (recreation, local competition, prefectural competition, distinct competition, or national competition), number of days of training per week, number of hours of practice per day on weekdays and weekends, frequency of participation in games (never, seldom, sometimes, or often), and practice intensity (not hard or hard) (Sekiguchi et al 2017). The following continuous variables were divided into different categories according to the number distribution: number of days of training per week (≤ 4 and > 4 days); number of hours of practice per day on weekdays (≤ 2 and > 2 hrs); and number of hours of practice per day on weekends (≤ 3 and > 3 hrs).…”
Section: Assessment Of Covariatesmentioning
confidence: 99%